AN EMPIRICAL STUDY OF THE FORMATION OF ADDICTIVE BEHAVIOR IN ADOLESCENTS - Mamadjonova Shokhista Kamoldinovna (Bright Mind Publishing, 2025)
This article studies the types of addictive behavior that adolescents are prone to, depending on age and gender, and makes a psychological analysis. Based on the results of the study, a conclusion is drawn.
Keywords: Adolescence, addictive behavior, boys, addiction to gambling, addiction to food, addiction to alcohol.